Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk CV Alunga Berkah Abadi Pada Brand Otsky - Aqshal Fadhlilah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Competition in the fashion industry is becoming increasingly fierce due to the development of people’s clothing style trends which emphasize product quality at affordable prices. This condition requires the OTSKY brand to implement the right strategy to influence consumer purchasing decisions. This study aims to determine the effect of price and product quality on the purchasing decision of CV Alunga Berkah Abadi’s OTSKY brand products. The research uses a quantitative method by distributing questionnaires to 100 respondents. The data analysis technique used is multiple linear regression with t-test, F-test, and coefficient of determination tested using SPSS. The t-test results show that the price variable (X1) has a Tcount of 2.724 with a significance of 0.008, while the product quality variable (X2) has a Tcount of 4.925 with a significance of 0.000. Both values are greater than the Ttable 1.9847, indicating a significant partial effect. The F-test result shows an Fcount of 107.337 with a significance of 0.000, greater than the Ftable 3.939, indicating that price and product quality have a significant simultaneous effect. The coefficient of determination (R²) is 0.689, meaning that 68.9% of purchasing decisions are influenced by price and product quality, while the remaining 31.1% are influenced by other factors not examined in this study. The conclusion of this research is that price and product quality have a positive and significant effect, both partially and simultaneously, on purchasing decisions for OTSKY products.